2019
DOI: 10.3390/ijms20215431
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Sphingomyelinase Modulation in the Protective/Preventive Role of rMnSOD from Radiation-Induced Damage in the Brain

Abstract: Studies on the relationship between reactive oxygen species (ROS)/manganese superoxide dismutase (MnSOD) and sphingomyelinase (SMase) are controversial. It has been demonstrated that SMase increases the intracellular ROS level and induces gene expression for MnSOD protein. On the other hand, some authors showed that ROS modulate the activation of SMase. The human recombinant manganese superoxide dismutase (rMnSOD) exerting a radioprotective effect on normal cells, qualifies as a possible pharmaceutical tool to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Importantly, rMnSOD counteracts the radiation-induced liver damage exerting a protective role via acid sphingomyelinase (aSMase), and a preventive role via neutral sphingomyelinase (nSMase) [16]. Cataldi et al also demonstrated that nSMase is responsible for the preventive and protective effect elicited by rMnSOD against radiation-induced damage in the brain [17].…”
mentioning
confidence: 99%
“…Importantly, rMnSOD counteracts the radiation-induced liver damage exerting a protective role via acid sphingomyelinase (aSMase), and a preventive role via neutral sphingomyelinase (nSMase) [16]. Cataldi et al also demonstrated that nSMase is responsible for the preventive and protective effect elicited by rMnSOD against radiation-induced damage in the brain [17].…”
mentioning
confidence: 99%
“…The specific experimental model used for the present study permitted us to simultaneously investigate the effect of ionizing radiation and the protective/preventive effect of rMnSOD against radiation-induced liver damage. This was a unique opportunity under a collaborative project among Italian research groups and the Joint Institute for Nuclear Research, Dubna (Russia) [22]. Our results provide evidence that both prominent signs of pyroptosis (i.e., the loss of cell membrane integrity and the overexpression of Caspase-1) are induced by radiation treatment in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 57%
“…Our previous studies indicated that radiation targets SMase in the thyroid [20,21] and brain [22]. As there are two SMases involved in the apoptotic process (lysosomal aSMase and endoplasmic reticulum/nucleus nSMase1), we defined their behavior in the liver, where radiation upregulated Caspase-1, thereby triggering pyroptosis.…”
Section: Changes Of Sphingomyelin Metabolismmentioning
confidence: 99%
See 2 more Smart Citations